Degradation of pesticides chlorpyrifos, cypermethrin and chlorothalonil in aqueous solution by TiO2 photocatalysis - Affam, A.C. (2013)
Degradation of pesticides chlorpyrifos, cypermethrin and chlorothalonil in aqueous solution by TiO2 photocatalysis under UVA (365nm) irradiation was examined. Enhancement of degradation and improvement in biodegradability index (BOD5/COD ratio) by H2O2 addition were also evaluated. UVA irradiation per se produced insignificant degradation of the pesticides. In UV/TiO2 photocatalysis (TiO2 1.5gL-1, pH 6 and 300min irradiation), COD and TOC removal were 25.95 and 8.45, respectively. In UV/TiO2/H2O2 photocatalysis (TiO2 1.5gL-1, H2O2 100mgL-1, pH 6 and 300min irradiation), COD and TOC removal were 53.62 and 21.54, respectively and biodegradability index improved to 0.26. Ammonia-nitrogen (NH3-N) decreased from 22 to 7.8mgL-1 and nitrate-nitrogen (NO3--N) increased from 0.7 to 13.8mgL-1 in 300min, indicating mineralization. Photocatalytic degradation followed pseudo-first order kinetics with rate constant (k) of 0.0025 and 0.0008min-1 for COD and TOC removal, respectively. FTIR spectra indicated degradation of the organic bonds of the pesticides. UV/TiO2/H2O2 photocatalysis is effective in degradation of pesticides chlorpyrifos, cypermethrin and chlorothalonil in aqueous solution. UV/TiO2/H2O2 photocatalysis may be applied as pretreatment of a chlorpyrifos, cypermethrin and chlorothalonil pesticide wastewater at pH 6, for biological treatment. Â© 2013 Elsevier Ltd.